Enhanced and Balanced Charge Transport Boosting Ternary Solar Cells Over 17% Efficiency. Issue 34 (19th July 2020) - Li, Danqin; Zhu, Lei; Liu, Xianjie; Xiao, Wei; Yang, Jianming; Ma, Ruru; Ding, Liming; Liu, Feng; Duan, Chungang; Fahlman, Mats; Bao, Qinye
Abstract: Ternary architecture is one of the most effective strategies to boost the power conversion efficiency (PCE) of organic solar cells (OSCs). Here, an OSC with a ternary architecture featuring a highly crystalline molecular donor DRTB‐T‐C4 as a third component to the host binary system consisting of a polymer donor PM6 and a nonfullerene acceptor Y6 is reported. The third component is used to achieve enhanced and balanced charge transport, contributing to an improved fill factor (FF) of 0.813 and yielding an impressive PCE of 17.13%. The heterojunctions are designed using so‐called pinning energies to promote exciton separation and reduce recombination loss. In addition, the preferential location of DRTB‐T‐C4 at the interface between PM6 and Y6 plays an important role in optimizing the morphology of the active layer. Abstract : A highly efficient organic solar cell with a ternary architecture is successfully demonstrated by enhancing and balancing charge transport as well as matching integer charge transfer energy in a bulk heterojunction blend. As a result, a power conversion efficiency of 17.13% is obtained with the significantly improved fill factor of 0.813.